Comparison of atezolizumab plus bevacizumab and lenvatinib in terms of efficacy and safety as primary systemic chemotherapy for hepatocellular carcinoma. Issue 7 (25th April 2022) - Maesaka, Kazuki; Sakamori, Ryotaro; Yamada, Ryoko; Doi, Akira; Tahata, Yuki; Miyazaki, Masanori; Ohkawa, Kazuyoshi; Mita, Eiji; Iio, Sadaharu; Nozaki, Yasutoshi; Yakushijin, Takayuki; Imai, Yasuharu; et al.
Abstract: Aim: Atezolizumab plus bevacizumab and lenvatinib have each shown efficacy as primary systemic chemotherapies for hepatocellular carcinoma (HCC) in clinical trials. However, comparative trials of these two treatments have not been conducted. This study aimed to compare the therapeutic outcomes of these two treatments. Methods: This prospectively registered multicenter study analyzed 272 patients with HCC who received atezolizumab plus bevacizumab (the Atezo + Beva group; n = 90) or lenvatinib (the Len group; n = 182) as primary systemic chemotherapy. After propensity score matching (PSM), 66 patients were assigned to each group. Results: After PSM, the median progression‐free survival (PFS) was significantly longer in the Atezo + Beva group than in the Len group (8.8 vs. 5.2 months; p  = 0.012). No significant differences were noted between the two groups in terms of median overall survival (not reached vs. 20.6 months; p  = 0.577), objective response rates (43.8% vs. 52.4%; p  = 0.330), and disease control rates (76.6% vs. 82.5%; p  = 0.404). The percentage of patients with modified albumin‐bilirubin grades of one or 2a was maintained during treatment in the Atezo + Beva group but decreased over time in the Len group. The rate of discontinuation due to adverse events (AEs) was lower in the Atezo + Beva group than in the Len group (12.1% vs. 28.8%; p  = 0.018). Conclusions: Atezolizumab plus bevacizumab showed prolonged PFS, maintained hepatic reserve, and had lower rates of severe AEs compared with that on using lenvatinib as primary systemic chemotherapy for HCC.